PENEGAKAN HUKUM PIDANA TERHADAP KURIR MARKETPLACE PENGANTAR BARANG YANG MENYELESAIKAN ORDER TRANSAKSI ELEKTRONIK FIKTIF - Nurlina Husnita; Nella Sumika Putri; Ajie Ramdan (Paulus Law Journal, 2022)
Technological developments in the digital era have given rise to marketplace platforms that provide convenience in conducting buying and selling transactions online. The existence of promos in the marketplace platform raises the attraction for the community. In practice there are occnums who make fictitious electronic transactions to get a large number of promos. Delivery marketplace couriers have an important role in the completion of fictitious electronic transaction orders. The act of fictitious electronic transactions is a criminal offense as Article 378 of the Criminal Code and Article 35 of the ITE Jo Law. Article 51 Paragraph (1) of the ITE Law. Although involved in a criminal offense, the reality is that the courier is not carried out by criminal law enforcement. This research aims to examine the enforcement of criminal law against delivery marketplace couriers. This research uses legal research methods to answer problems. The results showed that there were several factors and obstacles that made criminal law enforcement against delivery marketplace couriers who completed fictitious electronic transaction orders ultimately not carried out.